DIGITAL INSTRUMENT FOR INFANT AND TODDLER MORTALITY REVIEW USING USER-CENTERED DESIGN METHOD - Royan Dwi Saputra; Rahmat Izwan Heroza; Dwi Rosa Indah; Allsela Meiriza; Pacu Putra; Ermatita Ermatita (Kresnamedia Publisher, 2022)
Abstract The Infant Mortality and Toddler Mortality rates are still relatively high in Indonesia. Data from the South Sumatra Health Office shows a relatively high number of infant and toddler mortality cases in Banyuasin and Musi Banyuasin Regency, with about 68 and 51 cases in 2017. Through the Program Kerja Sama (PKS) of the family health directorate of the health ministry of the Republic of Indonesia and the Public Health Faculty of Sriwijaya University. Find problems related to the absence of instruments in digital form, which are useful for conducting studies on infant and under-five mortality problems in health facilities, which were expected to assist in recording and reporting the review process run more effectively and efficiently. This research uses the User-Centered Design (UCD) method because it optimizes the application prototype according to the needs and desires of the end-user, which in this case is the health worker in the Health Facilities in Banyuasin and Musi Banyuasin Regency. The UCD method phases include understanding the use context, specifying the user requirements, designing the solutions, and evaluating against requirements. The results of the study were that the average usability score was 94, meaning that this application's prototype has been made according to the needs and desires of end-users. Also, the prototype of this application is feasible to implement.